Factors that influencing the effectiveness of hotel’s digital marketing / Nur Afifah Mohd Nor and Nur Athirah Ibrahim - Mohd Nor, Nur Afifah; Ibrahim, Nur Athirah (2021)
This research was conducted to analyze the factors that influence the effectiveness of a hotel's online marketing. Online marketing is the promotion of products or brands online. In recent days, digital marketing demand in hotels has become extremely strong with Social Media Marketing (SMM) working with social networking sites and Search Engine Optimization making the website appear in Google Ads and Online Magazine Search Engine Marketing (SEM) search results, video marketing through YouTube and websites are the types of digital marketing. The problem statement of this research is constantly evolving of the hospitality industry to remain competitive in a global business environment. It is also extremely important to recognize that the market is now guided by convenience and experience and that change is required to keep up with rivalry. Successful hotels will have digital marketing to support the business and achieve their goals. The objective of the research is to identify factors that influenced the effectiveness of a hotel's online marketing and the most significant factor contributing to the effectiveness of a hotel's online marketing. Next, the method used in this research is the secondary method using books, articles, journals, research reports , and web articles. These articles are compiled from previous research and summarised to improve the research's effectiveness. The findings of this research highlight the most significant factor contributing to the effectiveness of hotel's online marketing. For recommendations to future researchers, they must revise extensively to find relevant data for the research topic. In contrast, the researcher can use a qualitative method for this study, which entails conducting a survey and questionnaire. By using this method, the researcher will be able to collect more data from the questionnaire that they obtained. Moreover, the hotel industry may improve the online marketing strategy to boost their revenue and increase brand awareness.